Plasmodium vivax vaccine research – we've only just begun. Issue 2 (February 2017) - Tham, Wai-Hong; Beeson, James G.; Rayner, Julian C.
Graphical abstract: Highlights: Blood-stage vaccine development is particularly critical for Plasmodium vivax. Large-scale protein arrays are powering an expansion in vaccine antigen screening. Structural studies allow antigen design to focus on critical pan-reactive epitopes. Further information on immune mechanisms and antigen diversity is needed. Abstract: Plasmodium vivax parasites cause the majority of malaria cases outside Africa, and are increasingly being acknowledged as a cause of severe disease. The unique attributes of P. vivax biology, particularly the capacity of the dormant liver stage, the hypnozoite, to maintain blood-stage infections even in the absence of active transmission, make blood-stage vaccines particularly attractive for this species. However, P. vivax vaccine development remains resolutely in first gear, with only a single blood-stage candidate having been evaluated in any depth. Experience with Plasmodium falciparum suggests that a much broader search for new candidates and a deeper understanding of high priority targets will be required to make significant advances. This review discusses some of the particular challenges of P. vivax blood-stage vaccine development, highlighting both recent advances and key remaining barriers to overcome in order to move development forward.